AN NMR STUDY OF SINGLE- AND TWO-PHASE FLOW IN FAULT GOUGE FILLED FRACTURES - Chen Q.; Kinzelbach W. (My University, 2002)
The characteristics of single- and multiphase flow through fractured rock are of considerable interest in petroleum and natural gas exploitation as well as in the risk assessment of underground repositories. Flow processes of water and gas were studied in a granite core containing a fault gouge filled fracture zone. The pore structure of the sample was scanned by X-ray computed tomography (CT).A reversible change of fracture aperture due to shrinking and swelling of fault gouge was observed when drying, saturating and again drying the core. There is evidence that the fractures at the contact between matrix and fault gouge contribute most to permeability.Changes in the size distribution of water filled pores were monitored by low magnetic field nuclear magnetic resonance (NMR) during miscible flooding with deuterated water and immiscible flooding with nitrogen gas. Gas breakthrough occurred quickly at extremely low gas saturation indicating preferential pathways. Water saturation decreased gradually with the increase of injection pressure. In comparison, the process of miscible flooding showed a much more homogeneous behavior. Deuterated water breakthrough occurred slowly and at higher deuterated water saturation. In miscible flooding, the large and small range of the pore size distribution decreased simultaneously indicating that deuterated water invaded both types of pores at the same time. In the immiscible flooding process, the large pores were preferentially invaded by gas. At low water saturation, water only fills the very small pores, which do not contribute to gas flow.
Keywords: NUCLEAR MAGNETIC RESONANCE; FLOW IN FRACTURES; FAULT GOUGE; MISCIBLE FLOODING; IMMISCIBLE FLOODING